Arsenic burden in e-waste recycling workers – A cross-sectional study at the Agbogbloshie e-waste recycling site, Ghana - Yang, Jennie; Bertram, Jens; Schettgen, Thomas; Heitland, Peter; Fischer, Damian; Seidu, Fatima; Felten, Michael; Kraus, Thomas; Fobil, Julius N.; Kaifie, Andrea (Chemosphere, 2020)
The export of e-waste from industrialized to developing countries has led to the formation of a large-scale informal e-waste recycling sector in Accra, Ghana. During recycling processes, workers are exposed to several hazardous substances, such as heavy metals. As a common component of e-waste, inorganic arsenic can be released during e-waste recycling processes. The aim of this study was to assess the exposure to inorganic arsenic species in e-waste workers compared to a control group. N = 84 e-waste workers and n = 94 control subjects were included in this analysis. Inorganic arsenic species were determined in urine samples using HPLC-ICP-MS. E-waste workers showed higher median concentrations of As(III), As(V), MMA, DMA and the sum of inorganic arsenic in comparison to the control group. More than 80% of the e-waste workers exceeded the acceptable concentration (14 μg/L), which was significantly higher in comparison to the control group (70%). The tolerable concentration (40 μg/L) was exceeded in 17.2% of the participants, meaning a statistically relevant risk of developing cancer due to arsenic exposure throughout their (working) life. In conclusion, the exposure to inorganic arsenic is not only a problem of informal e-waste recycling, but a major public health concern that needs further investigation.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Contamination; Environment; Exposure; Heavy metal; Occupation; Public health